A STUDY OF THE RELATIONSHIP BETWEEN SOCIAL RESPONSIBILITY AND EARNING MANAGEMENT AND ITS REFLECTION ON THE FINANCIAL PERFORMANCE OF A SAMPLE OF COMPANIES LISTED ON THE IRAQ STOCK EXCHANGE - Maytham Bader Bawie Al-Sfan (Scholar Express Journals, 2023)
The aim of the research is to study the relationship between social responsibility and Earning management and the extent to which this relationship is reflected on the financial performance of a sample of banks listed in the Iraq Stock Exchange. The study was conducted on a sample of (20) banks for a period of (6) years from 2015 to 2020, and the researcher relied on The financial statements and disclosures attached to the research sample during the study period in measuring the variables which are social responsibility as an independent variable, and financial performance represented by (return on equity and return on assets) as a dependent variable, and Earning management as a mediating variable in the relationship and it was measured using Miller model, as the researcher relied on (Excel - SPSS) program in testing the relationship between the variables, and the researcher concluded that there is a significant impact of social responsibility activities in the management of Earnings, and this relationship has a significant impact on financial performance, and the study recommended the need to urge companies to perform social activities within the framework of the ethical dimension, which would contribute to Developing the community and publishing annual reports that include information on its social responsibility, along with the annual financial reports, in order to achieve integration between financial and financial performance environmental and social.
Keywords: social responsibility; Earning management; financial performance.